The 'new financial development paradigm' : the role of the state vis-a-vis the financial market in east Asia. - Lehmann, Jeanine Andrea. (2013)
This dissertation addresses the two-folded question of what role the contemporary East Asian state adopts with regards to the 'new financial development paradigm' and